Changes In The Physical Properties Of Previously Irrigated Light Sandy Meadows And Newly Irrigated Soils Of Mirzachol Under The Influence Of Deflation (Journal of Pedagogical Inventions and Practices, 2024)
The article presents changes in the physical properties of old-irrigated light sandy meadows of Mirzachul and newly irrigated soils under the influence of deflation, the results of monitoring various deflationary processes on irrigated lands. Experiments were carried out. It is recommended to plant strip crops as agricultural crops to restore, increase and protect the fertility of wind-eroded soils.